Root Canal Morphology of Mandibular Permanent Incisors - A Cone-Beam Computed Tomographic (CBCT) Study - Kayastha, Pujan Kranti; Shrestha, Lipika; Shakya, Merina; Khanal, Nirmala (Journal of College of Medical Sciences-Nepal, 2025)
Background Proper knowledge of root canal anatomy is most important for the success of root canal treatment. The objective of this study to find the numbers and morphological characteristics of root and root canals of mandibular central and lateral incisors using cone beam computed tomography (CBCT). Methods Retrospective CBCT data of 194 patients were retrieved between January 2022 to December 2024. In this study 52 patients were included, with 170 mandibular incisors were included in the study. The number of roots and root canals, and the canal configuration according to Vertucci’s classification were analyzed. The effect of tooth type and gender on the occurrence of anatomical variations was evaluated. Results The occurrence of two root canals was found to be 27.6% in mandibular incisors with all tooth having single root. Male (18.82%) shows a high occurrence of two canals. Mandibular lateral incisors show a high (17.06%) occurrence of two canals. According to Vertucci’s canal configuration, Type I (71.8%) has a higher occurrence, followed by Type II (15.9%), Type III (7.1%), Type V (2.9%), Type IV (1.8%), and Type VII (0.6%). Conclusions Type I was the most common type of canal configuration found in mandibular incisors followed by type II. Male shows almost double the occurrence of anatomical variations on mandibular incisors. Mandibular lateral incisors show a high occurrence of anatomical variations.